Antibacterial activity of bovine milk lactoferrin on the emerging foodborne pathogen Cronobacter sakazakii: Effect of media and heat treatment. (January 2015) - Harouna, S.; Carramiñana, J.J.; Navarro, F.; Pérez, M.D.; Calvo, M.; Sánchez, L.
Abstract: Cronobacter sakazakii is a pathogen transmitted by food, with high osmotic resistance and tolerance to desiccation, which affects mainly to newborns, infants and immunocompromised adults. C. sakazakii infection in infants has been associated with consumption of powdered milk. The purpose of this study was to evaluate the antibacterial activity of native and iron-saturated bovine lactoferrin (bLF) (from 0.5 to 5 mg/ml) on non-desiccated and desiccated C. sakazakii (10 4 CFU/ml) in different media (phosphate buffer, bovine skim milk and whey). In general, native bLF was the only effective form that inhibited growth of C. sakazakii in all media, its activity increasing with concentration and time of incubation. These results suggest that the antibacterial effect of bLF on C. sakazakii is mainly due to iron sequestration. However, iron-saturated bLF showed some effect by reducing the viability of C. sakazakii in whey. There has not been observed an increased sensitivity of desiccated bacteria to native bLF in phosphate buffer. However, although the antibacterial activity of native bLF against non-desiccated C. sakazakii was drastically reduced in milk or whey compared to phosphate buffer, there was a certain activity when it was assayed against desiccated cells in those media. The effect of some heat treatments on the antibacterial activity of native bLF was evaluated and only those of 72 °C for 15 s, 85 °C for 15 s, and 63 °C for 30 min maintained its whole activity. Highlights: Native bovine lactoferrin at 5 mg/ml reduces 8 log cycles Cronobacter sakazakii growth. Milk and whey diminish lactoferrin antibacterial activity against C. sakazakii. Pasteurization maintains lactoferrin antibacterial activity against C. sakazakii.